Impact of Rosacea on Keratinocyte Skin Cancers: A Prospective Case-Control Study of Basal and Squamous Cell Carcinoma Risk - Asli Aksu; Aysenur Demir; Hatice Gunay; Pinar Ozdemir Cetinkaya; Birgul Ozkesici Kurt; Hazel Ezgi Kaya; Ilknur Altunay; Deniz Altınel (Dermatology Practical & Conceptual)
Introduction: The full range of cutaneous comorbidities associated with keratinocyte skin cancers remains to be elucidated.